Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1302/0301-620x.95b6.31172
|View full text |Cite
|
Sign up to set email alerts
|

Additional surgical factors affecting the recurrence of hallux valgus after Ludloff osteotomy

Abstract: We reviewed 91 patients (103 feet) who underwent a Ludloff osteotomy combined with additional procedures. According to the combined procedures performed, patients were divided into Group I (31 feet; first web space release), Group II (35 feet; Akin osteotomy and trans-articular release), or Group III (37 feet; Akin osteotomy, supplementary axial Kirschner (K-) wire fixation, and trans-articular release). Each group was then further subdivided into severe and moderate deformities. The mean hallux valgus angle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
9
1
1
Order By: Relevance
“…Another finding in our study is that supplementary fixation with a locking plate leads to a significantly greater resistance to the lateral angle change. This can be correlated with the clinical observation that supplementary fixation -by means of Kwires-significantly reduced the loss of the postoperative correction of the first intermetatarsal angle (Choi et al, 2013). We are currently performing a prospective clinical study investigating the effect of supplementary fixation on any potential change of postoperative first intermetatarsal angle correction in patients with severe hallux valgus deformities.…”
Section: Accepted Manuscript 14mentioning
confidence: 64%
See 1 more Smart Citation
“…Another finding in our study is that supplementary fixation with a locking plate leads to a significantly greater resistance to the lateral angle change. This can be correlated with the clinical observation that supplementary fixation -by means of Kwires-significantly reduced the loss of the postoperative correction of the first intermetatarsal angle (Choi et al, 2013). We are currently performing a prospective clinical study investigating the effect of supplementary fixation on any potential change of postoperative first intermetatarsal angle correction in patients with severe hallux valgus deformities.…”
Section: Accepted Manuscript 14mentioning
confidence: 64%
“…Furthermore, since the entire load is transferred from the distal (dorsal) fragment to the proximal (plantar) through the fixation device there is a substantial force concentration at the small cortical bridge between the proximal drill hole and the osteotomy exit site at the dorsal aspect of the metatarsal which could potentially lead to a stress fracture and late displacement of the osteotomy. , in a clinical study Choi et al (2013) demonstrated that this kind of fixation significantly reduced the late loss of the postoperative correction of the first intermetatarsal angle. K-wire fixation has the advantage of ease of application and removal but very often causes traction and pain in the surrounding skin.…”
Section: Discussionmentioning
confidence: 92%
“…Several authors have reported an HV recurrence rate of (HVA ≥ 20 degrees) ranging from 4% to 30% following a proximal or shaft osteotomy of the first metatarsal, and these HV recurrence rates were observed in those with moderate to severe HV with a mean preoperative HVA ranging from 31 to 39 degrees. 4,5,16,21,23 To our knowledge, there have been no reports of postoperative recurrence rates in those with a severe HV deformity (HVA ≥40 degrees). A preoperative HVA of ≥40 degrees is significantly associated with postoperative recurrence of HV.…”
Section: Discussionmentioning
confidence: 98%
“… 16 To measure shortening of the first metatarsal length we used a method previously described by Trnka, et al 17 A bony callus at the osteotomy site was identified at the time of the early follow-up (6 to 8 weeks). As in previous studies, 18 , 19 we defined recurrence of hallux valgus as an HVA ≥20°. Recurrence was assessed at the final follow-up.…”
Section: Methodsmentioning
confidence: 99%